2020
DOI: 10.9734/ajmah/2020/v18i1030247
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy Outcomes in Egyptian Women on Maintenance Hemodialysis: A Multicenter Observational Study

Abstract: Background and Aims: Women in the childbearing period on hemodialysis (HD) have decreased fertility when compared with the general population. However, pregnancy in this patients’ population is still possible. The aim of the current study was to assess the conception rate in Egyptian HD females. Methods: The study comprises 2 phases: phase one studied the frequency of conception in HD females in Egypt, while phase two studied the live birth frequency and factors affecting it in 22 hemodialysis units (HDU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Four studies 17–21 evaluated neonatal mortality, but only three 17–19 presented the results adequately enough to allow meta‐analysis. Considering the estimated effect observed in the meta‐analysis, the wide CI gives imprecision to the result found, which are compatible with both the increase and the reduction in the risk of neonatal death with the use of any of the hemodialysis strategies (4/45 [8.8%] vs. 11/111 [9.9%]; Peto OR 0.85; 95% CI 0.26–2.80; 3 studies; 156 participants; I 2 = 21%; p = 0.79; very low certainty of evidence) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 17–21 evaluated neonatal mortality, but only three 17–19 presented the results adequately enough to allow meta‐analysis. Considering the estimated effect observed in the meta‐analysis, the wide CI gives imprecision to the result found, which are compatible with both the increase and the reduction in the risk of neonatal death with the use of any of the hemodialysis strategies (4/45 [8.8%] vs. 11/111 [9.9%]; Peto OR 0.85; 95% CI 0.26–2.80; 3 studies; 156 participants; I 2 = 21%; p = 0.79; very low certainty of evidence) (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The primary outcome of interest is the percent of women of reproductive age (15–50 years) on hemodialysis with amenorrhea. According to the statistics of the Ministry of Health, the number of these women is about 4,500 13 . A pilot study on 100 women revealed that 30% of these women have amenorrhea, with alpha errors of 5%, precision of 5%, and a design effect of 1.5 due to stratified sampling method.…”
Section: Population and Methodsmentioning
confidence: 99%
“…According to the statistics of the Ministry of Health, the number of these women is about 4,500. 13 A pilot study on 100 women revealed that 30% of these women have amenorrhea, with alpha errors of 5%, precision of 5%, and a design effect of 1.5 due to stratified sampling method. Thus, the calculated sample size was 452.…”
Section: Sample Sizementioning
confidence: 99%
See 2 more Smart Citations